Peroneural neuropathy after total hip arthroplasty with combined neural block: a case report - NISHIWAKI, Kimitoshi; TAMURA, Takahiro; KINUKAWA, Tomoaki Alex; SEKI, Taisuke; TAKEGAMI, Yasuhiko (Journal of Japan Society of Pain Clinicians, 2021)
A 46-year-old woman, 157 cm 58 kg, underwent left total hip arthroplasty after lumbar plexus block and sciatic nerve block via the parasacral approach. Postoperative X-ray revealed 20-mm leg extension. After surgery, both legs had movement disorder and sensory disturbance, which improved within a few hours. Lumbar plexus block was considered to be an epidural block. Thereafter, sensory and motor disorders slightly improved, but recovery of dorsiflexion movement of the left ankle joint was delayed and mild peroneal neuropathy at the level of the peroneal head was diagnosed by electromyography 28 days after surgery. Thirty-two days after surgery, the patient was discharged with stable walking using a cane. The neurological symptoms were suspected to be caused by physical factors, such as hyperextension of the peroneal nerve, because the neuropathy was at the level of the peroneum. We also cannot exclude the possibility that this nerve block affected paralysis.